2020
DOI: 10.25124/jmi.v20i3.3515
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Effects of Perceived Service Quality and Logistics Service Innovation on Repurchase Intention of Instant Courier Services through Customer Satisfaction and Trust

Abstract: Logistics are not only playing a significant role in the business process, but they can also add value to the business, and even also determine the life of the firm. Due to its significance, the advancement of logistics is inevitable. Customers want everything faster, and they are even willing to pay more for the service. This study provides an empirical investigation of instant courier service customers in Indonesia. A total of 300 valid questionnaires were collected and assessed using structural equation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
2
0
2
Order By: Relevance
“…Kualitas layanan telah berhasil ditingkatkan dalam menciptakan kepuasan pelanggan dan retensi pembelian, oleh karena itu memegang peran kunci dalam pemasaran dan logistik (Kusumawardani & Hastayanti, 2020).…”
Section: Kualitas Website Dan Kepercayaan Konsumenunclassified
“…Kualitas layanan telah berhasil ditingkatkan dalam menciptakan kepuasan pelanggan dan retensi pembelian, oleh karena itu memegang peran kunci dalam pemasaran dan logistik (Kusumawardani & Hastayanti, 2020).…”
Section: Kualitas Website Dan Kepercayaan Konsumenunclassified
“…Convention participation decision-making. The decision-making process typically involves consumers' various behavioural considerations before buying certain products (Kusumawardani and Hastayanti, 2020). Behavioural theories such as the theory of reasoned action (TRA) or the theory of planned behaviour (TPB) have widely been utilised in the current body of the literature to understand consumers' decision-making processes (Sahu et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several service managements studies have shown that service quality plays a key role in building trust (Chenet, Dagger, & O'Sullivan, 2010;Chiou & Droge, 2006). Logistic service quality has been considered to be one of the primary drivers of customer satisfaction (Fernandez, Lara, Ugalde, Sisodia, & Services, 2018;Kusumawardani & Hastayanti, 2020;E. Rachmawati & Suroso, 2020).…”
Section: Logistics Service Qualitymentioning
confidence: 99%